PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN BANK SYARIAH DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Tri Widianto; Supriyono Supriyono (STIE AUB Surakarta, 2018)
This research aims to know: 1) the influence of a leadership toward the employees performance, 2) the influence of an organization culture toward the employees performance, 3) the influence of a leadership toward the job satisfaction of the employee, 4) the influence of an organization culture toward the job satisfaction of the employee, 5) the influence of a job satisfaction toward the employees performance. The data are collected from 90 respondents by using a census method. They are analyzed through the research instruments such as a validity test by using a product moment test and the reliability test by using a cronbach alpha technique; path analysis; a determination coefficient (R2); t test; F test and direct and indirect effect. The research result shows that 1) the influence is positive significant of a leadership toward the employees performance, 2) the influence is positive significant of an organization culture toward the employees performance, 3) the influence is positive significant of a leadership toward the employees job satisfaction, 4) the influence is positive but not significant of an organization culture toward the employee job satisfaction, 5) the influence is positive significant of a job satisfaction toward the employee performance, 6) the influence is positive not significant of an organization culture toward the employee performance via employee job satisfaction, but the leadership influences positive significant toward the employee performance via the employee job satisfaction as intervening variable, 7) the coefficient determination the first similarity shows that R Square is 0,093 or 9.3%, means job satisfaction variable explains leadership and organization culture is 9.3% and while its remain 90.7% is explained by other variables which are not involved in the regression model such as a job environment and discipline, so that coefficient determination of the second similarity shows that R Square is 0.652 or 65.2%, means the performance explains a leadership, organization culture and job satisfaction is 65.2% and while its remain 34.8% is explained by other variable which is not involved in the regression model such as a job environment and discipline. Key word: leadership, organization culture, job satisfaction, performance